A Branch-and-Bound Algorithm for Multi-Level Fixed-Charge Problems - Jones, Arnold P.; Soland, Richard M. (Management Science, 1969)
Multi-level fixed-charge problems are mathematical optimization problems in which the separable portion of the objective function is the sum of piecewise continuous functions of a single variable. This paper describes a branch-and-bound algorithm that will find a global solution to this type of problem. The algorithm has the feature that a good feasible solution is generated at the start. Moreover, at each step of the algorithm an additional feasible solution may be generated for comparison with the best solution found previously.